Do the graphene nanoflakes pose a potential threat to the polychaete Hediste diversicolor?. (April 2021) - Urban-Malinga, Barbara; Jakubowska, Magdalena; Hallmann, Anna; Dąbrowska, Agnieszka
Abstract: Graphene is a promising material with a wide range of future applications that could potentially lead to its transfer from numerous water and terrestrial sources to the sea, thus fate and effects of graphene in the marine ecosystem deserve attention. Within this work, the impact of the short- and long-term exposure (36 h and 24 days) of the marine benthic polychaete Hediste diversicolor to various concentrations (36 h: 0.4, 4, 40 and 400 mg L −1 ; 24 days: 4 and 40 mg L −1 ) of the pristine graphene multilayer nanoflakes (of thickness 8–12 nm) was investigated. Experiments revealed a limited toxic effect of graphene on H. diversicolor . Although the polychaetes ingested graphene, no impact on their total energy content was found. The toxic effect expressed by significant elevation of catalase activity indicating activation of defence mechanisms was recorded but only at the early stage of exposure. Activities of other antioxidant and cellular damage biomarkers (SOD, GST, GSH, MDA, CBO) remained unaffected. Moreover, no neurotoxic effect expressed by inhibition of acetylcholinesterase (AChE) activity was observed. Substantial inter-individual variability in the activities of some biomarkers at the end of the long-term experiment was found. Polychaetes were buried deeper in the sediment with graphene than in the controls indicating an escape reaction and avoidance behaviour. The latter may lead to the transfer of graphene from the sediment surface to deeper sediment layers with unknown consequences for the benthic ecosystem. Graphical abstract: Image 1 Highlights: Pioneer studies of the ecotoxicity of graphene nanoflakes on Hediste diversicolor . A variety of biomarkers for monitoring of the 2 D materials effect on biota. Graphene nanoflakes from the ecological, chemical and physical perspective. Preliminary results for future standards in nanomaterials ecotoxicology. The basic research discussion on the consequences of nanomaterial for benthic systems.